Aminopeptidase N as a potential drug target - Farsa, Oldřich; Ballayová, Veronika; Žáčková, Radka; Zubáč, Peter (EUROPEAN PHARMACEUTICAL JOURNAL, 2023)
Aminopeptidase N (APN) is a broad specificity zinc metallopeptidase with many functions that do not always depend on its enzymatic activity. Among others, it is involved in tumor angiogenesis and metastasizing and also serves as a cellular receptor of some coronaviruses. Some APN inhibitors, such as bestatin or tosedostat, were used or tested as anticancer drugs in the past. Within the past two decades, we have prepared several series of potential APN inhibitors. Some of them reached interesting values of inhibitory activity and were also successfully tested for antiproliferation activity in cancer cell lines. We also performed some QSAR studies with APN inhibitors prepared by us and other authors.